2013
DOI: 10.1021/am403203q
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Inspired Anti-Oil-Fouling Chitosan-Coated Mesh for Oil/Water Separation Suitable for Broad pH Range and Hyper-Saline Environments

Abstract: Here, we report a bio-inspired chitosan (CS)-based mesh with high separation efficiency, oil-fouling repellency, and stability in a complex liquid environment. The surface of the CS coating maintains underwater superoleophobicity and low oil adhesion (<1 μN) in pure water and hyper-saline solutions, and it can keep stable special wettability in broad pH range environments after the CS mesh is fully cross-linked with glutaraldehyde and then reduced by sodium borohydride to form a stable carbon-nitrogen single b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
102
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 210 publications
(105 citation statements)
references
References 35 publications
2
102
0
1
Order By: Relevance
“…27 Li et al functionalized commercial textile with layered double hydroxide microcrystals and low surface energy molecules. [30][31][32] One of the drawbacks is that these materials will easily lose their functions when subjected to mechanical force, acidic/alkali, organic solvents, or high temperature. 29 The resulted sponges showed high separation efficiency for oil/water mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…27 Li et al functionalized commercial textile with layered double hydroxide microcrystals and low surface energy molecules. [30][31][32] One of the drawbacks is that these materials will easily lose their functions when subjected to mechanical force, acidic/alkali, organic solvents, or high temperature. 29 The resulted sponges showed high separation efficiency for oil/water mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…Among various liquids separation methods, membrane technique is regarded as a low-cost, effective, and environment friendly choice that has drawn considerable interest in last decade. Since the idea of taking the special wettability surface into the application of oil/water separation was proposed, [ 1 ] the researchers have prepared a large number of materials for the separation of oil/water mixtures.[ 2-6 ] Such as nanofi ber textile, [7][8][9][10] 3D porous foams, [11][12][13][14][15][16] and mesh [17][18][19][20][21] were frequently used to achieve water/oil separation. Nonetheless, water/oil separation system cannot satisfy the complex liquid mixture requirement during real industry processes.…”
mentioning
confidence: 99%
“…[18][19][20][21][22] For example, Feng et al 18 reported a novel mesh film coating with both superhydrophobic and superoleophilic properties via a spray-and-dry method. [23][24][25][26] In this research, we are also using natural hydrophilic polymers to prepare oil/water separation membranes with low cost via a facile method. Xue et al 19 coated a stainless-steel mesh with superhydrophilic polyacrylamide hydrogel via a photoinitiated polymerization process.…”
Section: Introductionmentioning
confidence: 99%